Effects of practical work on student achievement and anxiety in geometry - Rosete, Ronaldo B. (2006)
The effects of practical work approach in teaching high school geometry on students' achievement and anxiety level in mathematics was studied in this paper. It employed both quantitative and qualitative approaches. Two intact classes in third year of a typical public high school in the Division of City Schools, Manila were used in this study. The researcher-made instruments, the Geometry Achievement Test and the Mathematics Anxiety Rating Scale, were employed. Results included that the use of hands-on practical work teaching approach enhanced student's achievement in geometry better than visual practical work. Qualitative result showed that students had difficulty in proving theorems and did poorly in solving geometry problems.